Development and evaluation of a novel robotic platform for gait rehabilitation in patients with Cerebral Palsy: CPWalker (2017)
The term Cerebral Palsy (CP) is a set of neurological disorders that appear in infancy or early childhood and permanently affect body movement and muscle coordination. The prevalence of CP is two–three per 1000 births. Emerging rehabilitation therapies through new strategies are needed to diminish the assistance required for these patients, promoting their functional capability. This paper presents a new robotic platform called CPWalker for gait rehabilitation in patients with CP, which allows them to start experiencing autonomous locomotion through novel robot-based therapies. The platform (smart walker + exoskeleton) is controlled by a multimodal interface that gives high versatility. The therapeutic approach, as well as the details of the interactions may be defined through this interface. CPWalker concept aims to promote the earlier incorporation of patients with CP to the rehabilitation treatment and increases the level of intensity and frequency of the exercises. This will enable the maintenance of therapeutic methods on a daily basis, with the intention of leading to significant improvements in the treatment outcomes.